2014
DOI: 10.1111/dme.12438
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity with glycaemic control and cardiovascular risk profile in 65 666 people with Type 2 diabetes from Germany and Austria

Abstract: This survey indicates that glycaemic control and cardio-metabolic risk profiles in people with type 2 diabetes are positively related to physical activity. The effects of physical activity were beneficial in younger as well as in older people. The high number of inactive people with diabetes underlines the need to promote physical activity and sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
(30 reference statements)
0
9
0
2
Order By: Relevance
“…Studies indicate that in patients with type 2 diabetes the CVD risk profile can be improved through regular PA (7)(8)(9). Furthermore, meta-analyses show an HbA 1c -lowering effect in patients with type 2 diabetes who engage in regular PA (8,10).…”
mentioning
confidence: 99%
“…Studies indicate that in patients with type 2 diabetes the CVD risk profile can be improved through regular PA (7)(8)(9). Furthermore, meta-analyses show an HbA 1c -lowering effect in patients with type 2 diabetes who engage in regular PA (8,10).…”
mentioning
confidence: 99%
“…T2D patients with comorbid psoriasis should be further encouraged to improve their metabolic status in order to lower the risk for complications. Lifestyle changes such as physical activity showed a positive influence on metabolic control, diabetes treatment, BMI, and cardiovascular risk profile in T2D patients [ 54 ]. Moreover, previous research indicated that physical activity is an effective treatment in psoriasis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current therapy of gestational hypertension include antispasmodic, antihypertensive, sedative and termination of pregnancy, all of them are symptomatic treatments after the onset, without safe and effective precaution (Abalos 2001;Amaral et al 2017). The benefits of physical activity on health, such as reducing the risk of essential hypertension, coronary atherosclerotic heart disease, and type 2 diabetes are well documented, but there is a gap between physical activity and the risk of gestational hypertension (Coenen 2018;Hermann et al 2014). If it proves to be effective, maybe physical activity can be used as an adjunct and preventive intervention for gestational hypertension.…”
Section: Introductionmentioning
confidence: 99%